Analisis Structural Equation Modelling (SEM) Efek Kepemimpinan Transformasional, Kepuasan Kerja dan Komitmen Organisasional Terhadap Kinerja Karyawan Perusahaan Pelayaran - Kurniawan, Thomas Aquinas; Nugroho, Sukmo Hadi (Universitas Trunojoyo Madura, 2024)
The purpose of this research is to analyze the influence of transformational leadership, job satisfaction and organizational commitment on employee performance through work motivation in shipping companies. The research used a questionnaire distributed online to collect data. Determining the research sample using a purposive sampling method, namely employees who work in shipping in the West Indonesia Region and Central Indonesia Time, namely 87 employees. To assess the strength of direct and indirect relationships between various variables, SEM and Partial Least Square (PLS) models were used. The results of this research indicate that transformational leadership has a significant effect on job satisfaction and organizational commitment. Job satisfaction has a positive and significant effect on work motivation. Organizational commitment has a positive and significant effect on work motivation and employee performance. Work motivation has a positive and significant effect on employee performance. Transformational Leadership has a positive and insignificant relationship to employee performance in a direct relationship and through an indirect relationship. Transformational Leadership has a significant relationship to work performance, mediated by organizational commitment and intervened by work motivation. Job satisfaction has an insignificant positive relationship with employee performance in a direct relationship, but job satisfaction has a positive and significant relationship with employee performance when intervened by work motivation.